Optimization of regeneration protocol of tomatoes - Akter, K T; Tasmin, S; Yeasmin, S; Islam, M R; Alam, M S; Mehedi, M N H (Bangladesh Journal of Nuclear Agriculture, 2025)
Tomato (Solanum lycopersicon) is a commercially important, nutrient-rich vegetable crop that faces significant yield challenges due to climate variability. To address these challenges and meet growing consumer demands, the development of new cultivars through in vitro mutagenesis has emerged as a promising approach for breeders’. Therefore, this study aimed to optimize an in vitro regeneration system for BINA developed tomato varieties through indirect tissue culture technology, which is crucial step for successful in vitro mutagenesis for inducing different stress tolerance. The regeneration potential of 8-day-old cotyledonary leaves was evaluated in three popular tomato varieties, namely Binatomato-11, Binatomato-12, and Binatomato-13. Emphasis was placed on utilizing minimal resources to develop a cost-effective protocol, where BAP, IAA, and IBA were used as plant growth regulators. Results revealed that Binatomato-11 showed superior performance, with the highest callus induction frequency, shoot initiation frequency (56.0 %). longest shoot (13.6 cm) and optimal shoot formation under the PGR combinations of 2.5 mgL-1 + 0.5 mgL-1, whereas the lowest performances was observed in Binatomato-12. Moreover, the regenerated shoots from the aforementioned combinations Binatomato-11 demonstrated the highest root initiation frequency (63.0 %) and the longest root length (15.5 cm) compared to other genotypes and combinations of growth regulators. These findings highlight the genotype-specific response in tomato regeneration and underscore the importance of an optimized protocol suited for specific varieties. The results open the way for efficient tissue culture-based improvement and future mutagenesis studies to develop stress-resilient tomato cultivars in Bangladesh. Bangladesh J. Nuclear Agric., 39(1): 61-75, 2025